Parallel computing research in India : A scientometric assessment of Indian publications output during 1998-2017 - Gupta, B. M.; Dhawan, S. M. (Collnet journal of scientometrics and information management, 2019)
The present study has examined research output of India in parallel computing, as indexed in Scopus database during 1998-17 on a series of biblometric measures, such as publications growth rate, global publications share, citation impact, national-level share of international collaborative papers, distribution of publications by broad subjects. In addition, the study discusses the citation profile of top organizations and authors from India in parallel computing, and the preferred media for research communication, and characteristics of highly cited papers. The study finds that India registered 23.32% growth rate, contributed 3.70% global publications share, published 14.73% share of its output as international collaborative publications, and averaged citation impact of 5.15 citations per paper in the subject during the period. Hardware research has been found to be most popular sub-area of research in parallel computing. India contributed 26.03% share of output in parallel computing in top 15 most productive journals, and 14 of its papers have been rated as highly cited papers each with 82 to 663 citations per paper.